Association of Staphylococcus aureus Colonization with the Evolving Neonatal Nasal Microbiome and the Impact of Intranasal Mupirocin. (4th October 2017) - Khamash, Dina; Voskertchian, Annie; Baltimore,; White, James; Hittle, Lauren; Mongodin, Emmanuel; Milstone, Aaron M
Abstract: Background: Little is known about the bacterial communities in the nares of critically ill neonates. Our objectives were to explore the evolving nasal microbiome in neonates who acquire Staphylococcus aureus ( S. aureus ) colonization and the impact of intranasal mupirocin on the nasal microbiome. Methods: In the setting of a tertiary care neonatal intensive care unit S. aureus control program where neonates are screened weekly using chromogenic agar cultures and treated with intranasal mupirocin if found to acquire S. aureus colonization, we identified 15 neonates, 8 who acquired S. aureus colonization (cases) and 7 who did not acquire S. aureus colonization (controls). Cases and controls were matched on chronologic age and systemic antibiotic exposure. DNA was extracted for amplification of the 16S rRNA gene (V3V4 region), followed by next-generation sequencing using Illumina MiSeq. Sequences were merged into consensus fragments by FLASH and submitted for high-resolution taxonomic assignment using Resphera Insight. Differentially abundant taxa and alpha diversity measures were detected utilizing a nonparametric difference test with p-value correction using the False Discovery Rate. Results: Compared with conventional bacterial culture results, sequencing identified S. aureus membership in residual culture samples of all neonates who acquired S. aureus colonization. Figure 1 illustrates statistically significant differences in abundant taxa comparing cases prior to S. aureus colonization and controls. Several species were more abundant in controls, including Corynebacterium propinquum and accolens and Rothia mucilaginosa. C. propinquum and accolens and Rothia mucilaginosa were also more abundant in neonates after treatment with intranasal mupirocin than before treatment. Conclusion: These data suggest that there are differences in bacterial taxa abundance in the nasal microbiome in neonates who do and do not acquire S. aureus colonization and in neonates before and after treatment with intranasal mupirocin. A single species may not provide sufficient resistance to S. aureus colonization, but a community of organisms may protect against colonization. Disclosures: J. White, Resphera Biosciences: Shareholder, Equity